2022
DOI: 10.1097/md.0000000000030408
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of elevated alanine aminotransferase (ALT) in pregnancy: A cross-sectional labor and delivery-based assessment

Abstract: Since liver tests are not routinely checked in pregnancy, the prevalence of abnormal liver tests and liver-related abnormalities in pregnancy in a US-based population is not known. We sought to determine the prevalence of abnormal alanine aminotransferase (ALT) among pregnant Individuals who present to labor and delivery for evaluation and to evaluate prevalence of underlying diagnosed liver conditions. Prospective study evaluating liver tests in consecutive samples obtained on the labor and delivery unit. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The true incidence of elevated LFTs during pregnancy is very difficult to establish because these tests are not routinely performed in all pregnant women and there is substantial heterogeneity among laboratories and centers regarding the definition of “normal” values of liver enzymes. However, some studies have shown that the prevalence of elevated LFTs is up to 5–13% [ 5 , 77 , 79 , 85 ], which is much higher than the canonic 3% prevalence of pregnancy-related liver disease [ 86 ], suggesting that there may be more to it than what was previously thought. Most studies have evaluated LFTs during the first trimester [ 77 , 85 , 87 , 88 ], showing that higher ALT levels are associated with an increased risk of future gestational diabetes [ 77 , 87 , 88 ], large-for-gestational-age babies [ 85 , 89 , 90 ], and pre-eclampsia [ 77 , 78 , 79 ].…”
Section: Other Causes Of Elevated Liver Enzymes: Hypotheses and Specu...mentioning
confidence: 99%
See 3 more Smart Citations
“…The true incidence of elevated LFTs during pregnancy is very difficult to establish because these tests are not routinely performed in all pregnant women and there is substantial heterogeneity among laboratories and centers regarding the definition of “normal” values of liver enzymes. However, some studies have shown that the prevalence of elevated LFTs is up to 5–13% [ 5 , 77 , 79 , 85 ], which is much higher than the canonic 3% prevalence of pregnancy-related liver disease [ 86 ], suggesting that there may be more to it than what was previously thought. Most studies have evaluated LFTs during the first trimester [ 77 , 85 , 87 , 88 ], showing that higher ALT levels are associated with an increased risk of future gestational diabetes [ 77 , 87 , 88 ], large-for-gestational-age babies [ 85 , 89 , 90 ], and pre-eclampsia [ 77 , 78 , 79 ].…”
Section: Other Causes Of Elevated Liver Enzymes: Hypotheses and Specu...mentioning
confidence: 99%
“…Most studies have evaluated LFTs during the first trimester [ 77 , 85 , 87 , 88 ], showing that higher ALT levels are associated with an increased risk of future gestational diabetes [ 77 , 87 , 88 ], large-for-gestational-age babies [ 85 , 89 , 90 ], and pre-eclampsia [ 77 , 78 , 79 ]. In other studies, altered LFTs were investigated in the third trimester (or at delivery), with a reported prevalence of 11–13% [ 5 ]. Elevated LFTs were not always explained with pre-existing or pregnancy-related liver disease (30–50%) [ 5 , 91 ], and more importantly, could be associated with a higher risk of complications [ 5 ].…”
Section: Other Causes Of Elevated Liver Enzymes: Hypotheses and Specu...mentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment for ICP patients and fetuses is limited to symptomatic support and close monitoring. In addition, although ALT and AST, which are commonly used indicators to reflect the degree of liver damage, have also received widespread attention, some studies have found that serum ALT and AST are also significantly elevated in pregnant women with ICP, just as liver function impairment occurs in normal population, suggesting that serum ALT and AST can be used as indicators to evaluate ICP-related adverse pregnancy outcomes ( Juusela et al, 2020 ; Ekiz et al, 2016 ; Kushner et al, 2022 ). However, there are few reports on whether the ratio of serum ALT/AST in ICP pregnant women is also higher than that in normal pregnant women and whether it is associated with ICP-related adverse maternal and neonatal outcomes.…”
Section: Introductionmentioning
confidence: 99%